Procedural and remote outcome among patients undergoing urgent trans-catheter aortic valve implantation. (25th November 2020) - Berkovitch, A; Segev, A; Finkelstein, A; Kornowski, R; Danenberg, H; Fefer, P; Vaknin Assa, H; Konigstein, M; Perlman, G; Maor, E; Orvin, K; Steinvil, A; et al.
Abstract: Background: Severe aortic stenosis patients suffer frequent heart failure decompensations events often requiring hospitalization. In extreme situations patients can be found with pulmonary edema and cardiogenic shock, unresponsive to medical treatment. Urgent trans-catheter aortic valve implantation (TAVI) has emerged as a treatment option for these high-risk patients. Methods: We investigated 3, 599 patients undergoing TAVI. Subjects were divided into two groups based on procedure urgency: patients who were electively hospitalized for the procedure (N=3, 448) and those who had an urgent TAVI (N=151). Peri-procedural complications were documented according to the VARC-2 criteria. In hospital and 1-year mortality rates were prospectively documented. Results: Mean age of the study population was 82±7, of whom 52% were female. Peri-procedural complication rates was significantly higher among patients with an urgent indication for TAVI compared to those having an elective procedure: valve malposition 3.6% vs. 0.6% (p-value=0.023), valve migration 3.2% vs. 0.9% (p-value=0.016), post procedure myocardial infarction 3.7% vs. 0.3% (p-value=0.004), and stage 3 acute kidney injury 2.6% vs. 0.5%, (p-value=0.02). Univariate analysis found that patients with urgent indication for TAVI had significantly higher in hospital mortality (5.8% vs. 1.4%, p-value<0.001). similarly, multivariate analysis adjusted for age, gender and cardio-vascular risk factors found that patients with urgent indication had more than 5-folds increased risk of in-hospital mortality (OR 5.94, 95% CI 2.28–15.43, p-value<0.001). Kaplan-Meier's survival analysis showed that patients undergoing urgent TAVI had higher 1-year mortality rates compared to patients undergoing an elective TAVI procedure (p-value log-rank<0.001, Figure). Multivariate analysis found they had more than 2-folds increased risk of mortality at 1-year (HR 2.27, 95% CI 1.53–3.38, p<0.001 compared to those having an elective procedure. Conclusions: Patients with urgent indication for TAVI have higher in-hospital mortality and higher peri-procedural complication rates. However, if these patients survive the index hospitalization, they enjoy good prognosis. Funding Acknowledgement: Type of funding source: None